Application of Dexter’s soil physical quality index: an Irish case study - Fenton O.; Vero S.; Schulte R.P.O.; O’Sullivan L.; Bondi G.; Creamer R.E. (Irish Journal of Agricultural and Food Research, 2017)
Historically, due to a lack of measured soil physical data, the quality of Irish soils was relatively unknown. Herein, we investigate the physical quality of the national representative profiles of Co. Waterford. To do this, the soil physical quality (SPQ) S-Index, as described by Dexter (2004a,b,c) using the S-theory (which seeks the inflection point of a soil water retention curve [SWRC]), is used. This can be determined using simple (S-Indirect) or complex (S-Direct) soil physical data streams. Both are achievable using existing data for the County Waterford profiles, but until now, the suitability of this S-Index for Irish soils has never been tested. Indirect-S provides a generic characterisation of SPQ for a particular soil horizon, using simplified and modelled information (e.g. texture and SWRC derived from pedo-transfer functions), whereas Direct-S provides more complex site-specific information (e.g. texture and SWRC measured in the laboratory), which relates to properties measured for that exact soil horizon. Results showed a significant correlation between S-Indirect (Si) and S-Direct (Sd). Therefore, the S-Index can be used in Irish soils and presents opportunities for the use of Si at the national scale. Outlier horizons contained >6% organic carbon (OC) and bulk density (Bd) values <1 g/cm3 and were not suitable for Si estimation. In addition, the S-Index did not perform well on excessively drained soils. Overall correlations of Si. with Bd and of Si. with OC% for the dataset were detected. Future work should extend this approach to the national scale dataset in the Irish Soil Information System.